The Distinctive Creativity Endeavour Model for Creative Thinking, an Expansion of the Osborn-Parnes Creative Problem Solving Approach - Steven, Baptist Steven (2006)
Creative Destruction a termed coined by Joseph Schumpeter in 1942 where new businesses, products and services are being created and in turn immediately self destruct to cater for newer models and like as consumers have become highly demanding and brand loyalty is almost impossible to attain. This phenomenon is taking the world by storm especially so in this new millennium of globalisation where businesses operate at such excruciating pace and stiff competition has become a norm. Demand for new inventions coupled with higher performance and speed have forced corporations to be able to keep pace with the rapid changes or be deemed obsolete and insignificant. Human resources that are highly creative yet critical and able to perform consistently under pressure are much sought after. However, the exact educational system that the human capital is subjected to in Malaysia has been consistently criticised to be overly rote in approach and exam-oriented which does not encompass the elements of creativity and exploration. How than are we to achieve fully developed nation status come year 2020 where a workforce that is dynamic, creative and able to face up to the challenges if the catalyst to progress is the very system that they are subjected to is non creative in nature? The research was borne from the notion that for creativity to flourish within a work environment that is constantly faced with pressure to perform and meet the challenges of the highly competitive business environment, employees need to be equipped with the necessary knowledge and skills to solve problems effectively as well as creatively as opposed to freedom from pressure. The need for acquiring skills pertaining to one’s pressure threshold level as well as being creatively inspired is necessary to access one’s preconscious level where active creativity lies. Many of the creative problem solving models seems not to take these two highly crucial elements (pressure threshold realisation and creative destruction) into consideration and the Distinctive Creativity Endeavour (DCE) Model proposes an alternative. The DCE model is an enhancement of the much acclaimed Osborn-Parnes Creative Problem Solving (CPS) approach. Various versions of the CPS and DCE programs were developed and subsequently tested via an experimental approach to determine the exact effect of incorporating those two new factors into a CPS framework. The use of a control group (PLA) was introduced where the program administered was a non-creative problem solving program done to determine the comparative effect of undergoing a creative problem solving program with a non-creative program. Testing was carried out at two intervals, mainly the pretest and posttest with the use of the Torrance Tests of Creative Thinking (TTCT) to determine creativity levels of participants undergoing the creativity programs. Two research hypotheses were used in the study, the first where there exists no significant differences between the various creativity programs and second there exists no significant difference between the various creativity programs on creativity measures of the TTCT. The multivariate analysis of variance (MANOVA); F(16,320)=3.396, p=0.005, Pillal’s Trace=0.581 that shows there is statistically significant difference between the posttest scores on the combined dependent variables. As such, there exists a significant difference between the programs that had incorporated either or both of the pressure threshold realisation and creative inspiration elements in a creative problem solving program as opposed to Osborn-Parnes CPS program void of the said elements or for the control group (PLA). The size effect, η2=0.145 is very large and significant. The results shows that the variation in the creativity scores associated to the creativity programs are significant, which means that the pressure threshold realisation and creative inspiration factors does have a strong bearing on the difference in creativity scores rendering the DCE, CPSI and CPSP programs effective. When the programs with the pressure and/or creative inspirational elements were analysed together (CDP program) compared to the standard CPS and PLA programs, there was significant differences; F(8,160)=4.18, p=0.005, Pillal’S Trace=0.35, with a very large effect size of η2=0.173. This proves that the incorporation of pressure threshold realisation and creative inspiration have a significant effect on participants creative ability compared to the CPS and PLA program. The Scheffe post-hoc multiple comparison indicate significant differences between the CDP-PLA program (p=0.001) and CDP-CPS (p=0.002) for the Creativity Index (CI) scores as well as the Average Standard Score (ASS).The Creativity Index (CI) scores shows that the DCE program was most effective in bringing about overall creativity with an approximate of 48% increase from pretest to posttest. When the two elements of pressure threshold realisation and creative inspiration were introduced separately via the CPSP and CPSI programs respectively, the percentage increase was approximately 15% each. However, hypothetically if the independent results of the two programs were combined it sums up to only 30% which is lower compared to having both factors combined together as in the DCE program. Thus, we conclude that there could be a cumulative effect when both those elements are presented together in a creative problem solving program as it enhances one’s creative ability. For the Norms Referenced measures of the TTCT, the standard fluency, originality and elaboration dimensions showed a marked increase from pretest to posttest for the DCE program as opposed to the other programs. All three measures show that having the pressure threshold realisation and creative inspiration elements together in a creative problem solving gives an enhanced effect on creative ability as compared to having them individually incorporated into a CPS program as in the case of the CPSI and CPSP program. There is reason to believe that performing at one’s pressure threshold level while being in a creatively inspired state does have a positive relationship with creative endeavour provided one is able to access the preconscious state. Creativity does not take place by mere compliance to some simple and common techniques but has more to do with the preconscious where inspiration and insight emerges and learning to access and tap that rich source of creative energy is proposed via the DCE Model